Problems of entrepreneurship development in the production sector in the Republic of Kazakhstan - Utegenov, E.K.; Maidyrova, A.B.; Iskakov, A.Zh. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The purpose of the article is to analyze the application of mechanisms for the development of entrepreneurial activity in the production sector of the Regions of Kazakhstan and develop proposals for its improvement. The research process uses such General scientific research methods as observation, description, analysis and synthesis, as well as comparative, formal-logical and other methods of cognition. As a research information base, statistical data and data on projects of JSC «Damu entrepreneurship Development Fund», which helps in the creation and development of small and medium-sized business projects in Kazakhstan, were used. This article demonstrates and analyzes current quantitative information on the number of enterprises in the field of small and medium-sized businesses in the regional and sectoral context. The forms and sources of financing are investigated; the features of development of small and medium-sized enterprises in the Republic of Kazakhstan are defined. The ways of development of entrepreneurship in the production sphere are suggested.